Kindness the Relationship between God and Creation (Global Journal of Human-Social Science, 2013)
In Islamic Gnosticism the basis of creation is inherent affection(Hob) of God toward its own essence. Then He resolved to observe its perfection in a perfect mirror. In the vision of erotic school's Gnostics this mirror is the existence of the prophet Mohammad (God's blessing be on him)-and consequently messengers and saints of God-who directly enjoyed the kindness (Mohabat) of eternal true-love (Mahbub) and through him He has created the universe. So the survival and continuity of creation is based on kindness and love. Only a Gnostic can understand this and also comprehend the epitome of all divine names and attributes-including kindness; because by controlling concupiscence on the one hand it has dominated on its body and senses through universal traveling and has tamed the world and on the other hand it has removed darkened and bodily veils of the heart through movement of soul in order to manage to see the beauty of God inwardly, and visit and join to him. In fact, he reached a position "in which the essence is abstracted from its all trends, desires and tendencies, so that its willing is raised and becomes the willing of God; that is, true-love, affection and Moheb become one thing.
Keywords: gnosticism; true-love; affection and Moheb